TRACER STUDY ALUMNI DALAM MENINGKATKAN MUTU AKADEMIK DI FAKULTAS TARBIYAH DAN ILMU KEGURUAN IAIN DANGSIDIMPUAN - ZULHIMMA, ZULHIMMA (Institut Agama Islam Negeri Padangsidimpuan, 2015)
Tracer Study is an effective media that is used to track the whereabouts and condition of alumni. Tracer study has a very important role in filtering the information of the alumni as an evaluation and development of the college towards a better. Alumni brings its own benefits for universities, either in academic and pragmatic fields, such as: updating of based curriculum relevant to the needs of the market / the world of work, utilization of alumni as guest lecturers, professional lecturers, seminars, training, etc